Sulfate-selective binding and sensing of a fluorescent [3]rotaxane host system. - Langton, M; Beer, P (2012)
The chloride-templated synthesis of a novel [3]rotaxane, capable of binding anionic guests, and incorporating a naphthalene group for fluorescence sensing is reported. Extensive (1)H NMR titration studies were used to probe the anion binding selectivity of the system. The rotaxane selectively recognises sulfate, undergoing an induced conformational change upon sulfate binding to form a 1:1 stoichiometric sandwich-type complex, concomitant with significant quenching of the fluorescence. Binding of mono-anionic guests results in the formation of a 2:1 stoichiometric guest-host complex, and a modest enhancement of the emission. Addition of an excess of sulfate in non-competitive solvent also results in a 2:1 emissive complex.